Exposure to environmental tobacco smoke: association with personal characteristics and self reported health conditions. Issue 10 (1st October 2001) - Iribarren, C; Friedman, G D; Klatsky, A L; Eisner, M D
Abstract : STUDY OBJECTIVE: To examine the association between exposure to environmental tobacco smoke (ETS) and demographic, lifestyle, occupational characteristics and self reported health conditions. DESIGN: Cross sectional study, using data from multiphasic health checkups between 1979 and 1985. SETTING: Large health plan in Northern California, USA. PARTICIPANTS: 16 524 men aged 15–89 years and 26 197 women aged 15–105 years who never smoked. RESULTS: Sixty eight per cent of men and 64 per cent of women reported any current ETS exposure (at home, in small spaces other than home or in large indoor areas). The exposure time from all three sources of ETS exposure correlated negatively with age. Men and women reporting high level ETS exposure were more likely to be black and never married or separated/divorced, to have no college or partial college education, to consume three alcoholic drink/day or more and to report exposure to several occupational hazards. Consistent independent relations across sexes were found between any current exposure to ETS and a positive history of hay fever/asthma (odds ratio (OR)=1.22 in men, 1.14 in women), hearing loss (OR=1.30 in men, 1.27 in women), severe headache (OR=1.22 in men, 1.17 in women), and cold/flu symptoms (OR=1.52 in men, 1.57 in women). Any current ETS exposure was also associated with chronic cough (OR=1.22) in men and with heart disease (OR=1.10) in women. Self reported stroke was inversely associated with any current ETS exposure in men (OR=0.27). No associations were noted for cancer or tumour and for migraine. CONCLUSION: ETS exposure correlated with several personal characteristics potentially associated with adverse health outcomes. Although the study design precluded causal inference, ETS exposure was associated with several self reported acute and chronic medical conditions.